Habitat openness and predator abundance determine predation risk of warningly colored longhorn beetles (Cerambycidae) in temperate forest - Goßmann, Anika; Ambrožová, Lucie; Cizek, Lukas; Drag, Lukas; Georgiev, Kostadin; Neudam, Liane; Perlík, Michal; Seidel, Dominik; Thorn, Simon (Journal of insect science (Online), 2023)
Organisms have evolved different defense mechanisms, such as crypsis and mimicry, to avoid detection and recognition by predators. A prominent example is Batesian mimicry, where palatable species mimic unpalatable or toxic ones, such as Clytini (Coleoptera: Cerambycidae) that mimic wasps. However, scientific evidence for the effectiveness of Batesian mimicry in Cerambycids in natural habitats is scarce. We investigated predation of warningly and nonwarningly colored Cerambycids by birds in a temperate forest using beetle dummies. Dummies mimicking Tetropium castaneum, Leptura aethiops, Clytus arietis, and Leptura quadrifasciata were exposed on standing and laying deadwood and monitored predation events by birds over one season. The 20 surveyed plots differed in their structural complexity and canopy openness due to different postdisturbance logging strategies. A total of 88 predation events on warningly colored beetle dummies and 89 predation events on nonwarningly colored beetle dummies did not reveal the difference in predation risk by birds. However, predation risk increased with canopy openness, bird abundance, and exposure time, which peaked in July. This suggests that environmental factors have a higher importance in determining predation risk of warningly and nonwarningly colored Cerambycidae than the actual coloration of the beetles. Our study showed that canopy openness might be important in determining the predation risk of beetles by birds regardless of beetles' warning coloration. Different forest management strategies that often modify canopy openness may thus alter predator-prey interactions.
Keywords: Birds; Ecosystem; predátorské chování; Predatory Behavior; Batesian mimicry; Animals; ekosystém; lesy; Coleoptera; Forests; beetle dummies; brouci; zvířata; ptáci; natural disturbance; management intensification